Dynamics of pro-oxidant/antioxidant homeostasis during acute cerebrovasular disorders (experimental modeling) - Khomut, Yu.; Savytskyi, I.; Savytskyi, V. (Journal of Education, Health and Sport, 2025)
Background. Acute cerebrovascular accidents, particularly ischemic stroke, are a leading cause of mortality and long-term disability worldwide. Oxidative stress and disruption of antioxidant defense systems play a central role in ischemic brain injury, yet the temporal dynamics of pro-/antioxidant imbalance remain insufficiently characterized. The aim. To assess changes in superoxide dismutase, catalase, citrate, diene conjugates, and total antioxidant activity in brain tissue homogenates and blood serum of rats with experimentally induced ischemic injury, in order to determine temporal patterns of oxidative and antioxidant imbalance. Materials and methods. The study was conducted on 60 white non-linear rats. Focal cerebral ischemia was induced via endovascular occlusion of the middle cerebral artery according to the Longa model. SOD activity was measured using the nitroblue tetrazolium reduction method, catalase activity by hydrogen peroxide decomposition, DC levels by UV absorption at 232 nm, and TAA via malondialdehyde formation. All experiments were conducted in accordance with GLP and ethical guidelines. Statistical analysis was performed using Student’s t-test and Fisher’s criterion, with p<0.05 considered significant. Within the first day of ischemic injury, TAA in serum increased by 49% relative to intact controls, indicating an early compensatory activation of antioxidant systems. Brain tissue showed decreased SOD and catalase activity with elevated citrate and DC levels, reflecting enhanced lipid peroxidation. By day 14, serum TAA sharply declined (16.3% below intact controls), while catalase activity remained low and DC levels continued to rise. Persistent SOD hyperactivation alongside inadequate catalase activity suggested accumulation of hydrogen peroxide and progressive oxidative stress. Conclusions: Acute cerebral ischemia induces a pronounced pro-oxidant shift centrally and systemically, triggering early oxidative damage. Prolonged ischemia depletes antioxidant defenses, exacerbating oxidative stress and tissue injury. The imbalance between SOD and catalase activities promotes hydrogen peroxide accumulation and may serve as a predictive marker of neurodegenerative processes following ischemic stroke.